Terorisme dan Media Massa: Debat Keterlibatan Media - Prajarto, Nunung (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2004)
This article examines the relationship between the government and the media, arguing that both the government and the media workers can create a compact cooperation against terrorism. This can be used for combating the media strategy applied by the terrorist groups which tend to enjoy conflict with violence to spread their propaganda. Matrixing the changing faces of terrorism and the medias role in a conflict helps to facitilitate the government in handling terrorism.